2019
DOI: 10.1177/2047487319891778
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear is not superior to linear aerobic training periodization in coronary heart disease patients

Abstract: Background We aimed to compare: (1) two different periodized aerobic training protocols (linear (LP) versus non-linear (NLP)) on the cardiopulmonary exercise response in patients with coronary heart disease; (2) the proportion of responders between both training protocols. Design A randomized controlled trial. Methods A total of 39 coronary heart disease patients completed either LP ( n = 20, 65 ± 10 years) or NLP ( n = 19, 66 ± 5 years). All patients completed a cardiopulmonary exercise testing with gas excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Patients above the median (Á peak VO 2 > 1.3 mL.min -1 .kg -1 ) were considered as high-responders; patients under or equal to the median or with a decrease in peak VO 2 were considered as lowresponders or as non-responders. Boidin et al 11 found that, in the LP and NLP groups, five and three patients were considered as non-responders, respectively, three and seven patients as low-responders, and 12 and nine patients as high-responders; no significant statistically difference between the two exercise programme groups was observed. Boidin et al 11 provide an important contribution to test different individualized progressive exercise testing models to optimize adaptations in CAD patients.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Patients above the median (Á peak VO 2 > 1.3 mL.min -1 .kg -1 ) were considered as high-responders; patients under or equal to the median or with a decrease in peak VO 2 were considered as lowresponders or as non-responders. Boidin et al 11 found that, in the LP and NLP groups, five and three patients were considered as non-responders, respectively, three and seven patients as low-responders, and 12 and nine patients as high-responders; no significant statistically difference between the two exercise programme groups was observed. Boidin et al 11 provide an important contribution to test different individualized progressive exercise testing models to optimize adaptations in CAD patients.…”
mentioning
confidence: 99%
“…In the present issue of this journal, Boidin et al. provide a meritorious paper 11 and they compare two different periodized aerobic sessions, linear (LP) versus non-linear (NLP), blindly randomized, in a 12-week supervised exercise programme on the cardiopulmonary exercise response in patients with CAD. All patients completed cardiopulmonary exercise testing (CPET): peak oxygen uptake (peak VO 2 ), oxygen uptake, efficiency slope, ventilatory efficiency slope (VE/VCO 2 slope), VO 2 at the first (VT1) and second (VT2) ventilatory thresholds, and oxygen pulse (O 2 pulse) were measured.…”
mentioning
confidence: 99%
See 3 more Smart Citations